THE ECONOMIC CRISIS VERSUS THE CRISIS OF ECONOMICS AS A SCIENCE - Fiedor, Bogusław (Ekonomika, 2013)
Abstract. The paper starts with arguments against forming causative links between crisis phenomena in the economy, both in its real and regulatory sphere, and the crisis of the economic science as such, in terms of its cognitive and predictive values. According to the author, it is also true with respect to the current economicfinancial crisis.The second part of the paper is an attempt of explaining what should be considered a ‘normal’ way of development of economic science. The author puts and justifies a thesis that this development is a journey of ideas being brought about by numerous causes, with a significant role played by inspirations related not to observation of the real world but to the ‘world of economists’ (ideas shared by academic communities) and the phenomena appearing in the external environment of economics as a science: new political and social ideologies, cultural and technological trends, as well as geopolitical changes.In the subsequent part of the paper, starting with the recognition of the so-called logical and historical factors in the development of economic science or, following the distinction made by D. Ross (2005), the distinction of philosophical and historical-sociological strategies in this development, the author tries to prove that over the last half-century the development of economic science has been heavily influenced by the broadening acceptance of the criterion of instrumental effectiveness (Laudan–Mongin) in the appraisal of its scientific progress. It is argued in the paper that this has the effect of diminishing the ability of economic science to recognize and explain some major contemporary civilizational and technological trends (a kind of crisis in terms of the cognitive realism criterion). However, with respect to the emergence of new and cognitively valuable schools and currents (e.g., New Institutional Economy), this should not be considered a common feature of today’s economics. Secondly, the increasing role attributed to the instrumental effectiveness criterion in the evaluation of progress in economic science, has resulted in some crisis phenomena with respect to the predictive strength of economic models and theories.The paper ends with some more general reflections attempting to identifiy the civilization and technological trends and structural changes in modern economies that are not sufficiently addressed and analyzed in the mainstream economics, thus leading to some crisis phenomena (but not a general crisis) in its development in terms of the cognitive, predictive, and utilitarian value. With regard to the latter (perceived from the point of view of various economic policies), the author postulates the need for a more eclectic approach. It is understood as a postulate to look for the nature, manifestations of and reasons for both growth and crisis processes in contemporary economies, as well as for the instruments of growth state policy, in various (sometimes even competing) theories and schools in today’s economics.Key words: economic crisis, crisis of economics as a science, criteria of scientific progress in economics, migration of economic ideas, logical and historical factors in the development of economic science, instrumental and cognitive realism, civilizational and technological trends